(untitled) (Oratio Directa, 2024)
Self-existence is a person's condition and ability to find meaning in life. This study examines self-existence through educational video content on the TikTok account @mayatoomuch. It uses symbolic interaction theory and the concepts of social media, TikTok, self-concept, and self-existence. The study applies a qualitative approach within the constructivist paradigm and a phenomenological method. Data were collected through observation, interviews, documentation, and triangulation. The findings show that Maya Rachmawaty's self-existence can be understood through four components of Edmund Husserl's phenomenology: intentionality, noesis and noema, intuition, and intersubjectivity. Self-existence on TikTok is maintained through consistent educational content, audience interaction, personal branding, and the continuing relevance of content to followers.